Perceived emotional intelligence of university professors based on the nature of the subject taught - Botey, M.; Vaquero-Diego, M.; Sastre, F.J. (Technological forecasting & social change, 2020)
•The teachers Emotional Intelligence profile is related to the of subject taught.•Humanities teachers need to improve emotion ‘Attention’, mainly in man.•Science teachers need to improve emotion ‘Clarity’. Perceived emotional intelligence (PEI) promotes coexistence and self-well-being. Every professor can improve their PEI throughout life by generating benefits for themselves, for the institution where they work, and especially for the student. This study focuses on identifying the characteristics of perceived emotional intelligence (PEI) between two groups of university professors. One group of professors teaches humanistic and sociological subjects while the other group teaches subjects traditionally called sciences. These results provide useful information to create innovative PEI training plans tailored to each group. Therefore, the development of the professors may have important impacts on the students. The Trait-Meta Mood Scale (TMMS-24) instrument is used to evaluate teachers’ PEI, and two methodologies are applied: Structural Equation Modelling (SEM) and Fuzzy-Set Qualitative Comparative Analysis (fsQCA). The results indicate the existence of significant relationships between PEI dimensions and the type of subject taught, and they also give “sufficient pathways” to identify the membership in each group of teachers (humanities or sciences).